Green Human Resource Management: A Review of Integration of Environment and HRM Practices in Hotel Industry - MOHANTY, Sasmita; MISHRA, Sitikantha; MOHANTY, Ashish (Journal of Environmental Management and Tourism, 2021)
The concept of ‘Green Human Resource Management Practices’ in hotel industry in gaining momentum in the recent times and has drawn a great deal of attention from the perspective of academia and the industry. This paper is a collage of reviews taken from the existing literature on the subject with a prime objective to explore about green human resource management practices in hotel industry. It has been observed after a careful perusal that green practices need a further extension from the existing practices of human resource management. The prime objective of this conceptual paper is to understand the need for green human resource practices in the hotel industry at large and to contribute towards the scope of green practices in human resources management for sustainable environmental performance.